2017
DOI: 10.1371/journal.pone.0181132
|View full text |Cite
|
Sign up to set email alerts
|

“The care is the best you can give at the time”: Health care professionals’ experiences in providing gender affirming care in South Africa

Abstract: BackgroundWhile the provision of gender affirming care for transgender people in South Africa is considered legal, ethical, and medically sound, and is—theoretically—available in both the South African private and public health sectors, access remains severely limited and unequal within the country. As there are no national policies or guidelines, little is known about how individual health care professionals providing gender affirming care make clinical decisions about eligibility and treatment options.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Multiple studies describe the arduous experiences of trans adults seeking healthcare [43][44][45][46][47][48][49][50][51][52]. Notably, most will report experiences of stigma and discrimination when accessing healthcare, from encounters with administrative staff to encounters with healthcare providers [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies describe the arduous experiences of trans adults seeking healthcare [43][44][45][46][47][48][49][50][51][52]. Notably, most will report experiences of stigma and discrimination when accessing healthcare, from encounters with administrative staff to encounters with healthcare providers [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding gendered power relations is fundamental for the LN, as a human rights-based network, to continue to inclusively advocate for health and human rights [ 57 ]. Despite progressive legislation, South Africa has profound gender inequality; women in South Africa are more likely to suffer health and rights violations, and there is emerging evidence that transgender and gender diverse people are systematically excluded from health policy and healthcare delivery [ 58 , 59 ]. Our findings suggest that the member organizations of the LN push for the empowerment of women.…”
Section: Discussionmentioning
confidence: 99%
“…The limited research in South Africa on transgender identities and experiences focuses primarily on psychomedical narratives of transgender identity and on the attitudes of health care workers toward gender diverse individuals (see Luvuno, Ncama and Mchunu 2017; Newman-Valentine and Duma 2014; Spencer, Meer and Müller 2017). Scholarship here evinces the frustrations and barriers to accessing gender-affirming health care—particularly medical transitioning (Husakouskaya 2013).…”
Section: Contextualizing Trans Masculinitiesmentioning
confidence: 99%
“…As in other nations, the cost of medical transition presents barriers to many transgender people seeking gender affirmative health care in South Africa. While Karabo self-funds his medical transitioning and can access private medical care, many transgender people in the country rely on an under-resourced and overwhelmed public health care system (Camminga 2019) with long waiting lists for accessing medical transitions (Spencer et al 2017). Most of the participants in this study had already begun the process of medical transitioning and reported relative ease in accessing gender-affirming health care as a result of their financial stability.…”
Section: Discursively Constructing Trans Masculinity In Cape Townmentioning
confidence: 99%